POLITICAL WILL OF STRATEGIES TO ADDRESS CHILD VIOLENCE - Berliana Putri; Ertien Rining Nawangsari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Indonesian government has responded to the increasing cases of child abuse with Government Regulation Number 78 of 2021 on Special Protection for Children. Despite Surabaya City having won the Child-Friendly City (KLA) award five times consecutively, challenges remain in reducing the number of child abuse cases. This study aims to analyze the political will in addressing child abuse by the DP3APP-KB Surabaya. The results show a strong commitment from DP3APPKB in responding to child abuse through the PUSPAGA and KAS-RPA programs, with a need for further steps to expand child protection coverage and strengthen collaboration. Child protection is a top priority for DP3APPKB Surabaya, as evidenced by the significant budget allocation in 2023. Effective political support mobilization strategies are evident through active communication, cross-sector coordination, and stakeholder collaboration. Public commitment and appropriate resource allocation are key pillars of DP3APPKB's success in implementing child protection programs. DP3APPKB also demonstrates commitment to enforcing laws related to child abuse cases with firm actions and inter-agency collaboration. Child protection efforts are ensured to be sustainable through a long-term approach, collaboration, policy development, and regular monitoring. Adaptation and learning are also recognized as integral parts of the evaluation of child protection programs.